Compuestos fenólicos y actividad antiinflamatoria in vitro de extractos de Euphorbia umbellata sobre eritrocitos plasmáticos - Huamán Andoa, Doris Jacqueline (2024)
Objective: determine the content of phenolic compounds and the anti inflammatory activity of E. umbellata extracts on plasma erythrocytes. Methodology: Samples of leaves and stems of E. umbellata collected following appropriate protocols were used. The extracts were obtained by standard techniques and analyzed for their content of total phenols, flavonoids and anthocyanins using UV-visible spectrophotometry. The anti-inflammatory activity was evaluated at concentrations of 10, 100, 500 and 1000 µg/mL using a plasma erythrocyte model. Results: Stems of E. umbellata exhibited significantly higher content of total phenolics, flavonoids and anthocyanins compared to leaves. Traces of catechins were detected in both parts of the plant. However, alcoholic extracts of leaves and stems did not show significant anti-inflammatory effects at the concentrations evaluated. Conclusion: E. umbellata extracts do not present anti-inflammatory activity at the concentrations examined. However, the detailed characterization of the profile of phenolic compounds and the evaluation of biological activity in other experimental models could reveal therapeutic or nutraceutical potential of this plant species.